HABITUS PENGEMBANGAN DESA WISATA KUWU: STUDI KASUS DESA WISATA KUWU KECAMATAN KRADENAN KABUPATEN GROBOGAN - Ariyani, Nur Indah; Demartoto, Agyo; Zuber, Ahmad (Jurnal Analisa Sosiologi, 2015)
This research aimed to find out the tourism potency, practice (habitusand domain capital), supporting and inhibiting dimensions, strategy, and theeffect of Kuwu Tourism Village Development in Kradenan Subdistrict ofGrobogan Regency of Central Java using Pierce F Bourdieu’s Practical Theory and Robert K. Merton’s Structural Functionalism Theory. This study was a qualitative research using case study strategy. The data source ofresearch included informant, archive and document. The sampling technique used was purposive sampling. Technique of collecting data used in thisresearch was in-depth interview and observation. The result of research show that many tourism potentials had not been explored yet in Kuwu Village,either social or cultural. Habitus and economic capital, social capital, cultural capital, and symbolic capital of Kuwu villagers could be utilized inKuwu tourism village domain to develop Kuwu tourism village. But in fact, the habitus and capital the Kuwu villagers had, had not been utilized anddeveloped optimally. The supporting dimensions in Kuwu tourism villagedevelopment included the presence of Bledug Kuwu natural phenomenon,social cultural potency, and accessible road. Meanwhile, the inhibitingdimension derived from government, community, physical condition andexternal parties (investor and Non Governmental Organization). The tourismdevelopment strategy was taken by regency government and villagegovernment, in which the development still focused on Bledug Kuwu tourismobject. The effect of Kuwu Tourism Village viewed from social economicaspect occurred only in some people obtaining additional income from theirparticipation in becoming food sellers, parking personnel and etc in BledugKuwu. The social cultural effect was the preserved Javanese traditional artwith the organization of art performance in Bledug Kuwu Tourism object. Theenvironmental effect could be seen only in the Kuwu (Krajan) Hamlet people who had disposed the rubbish in the permanent rubbish place. Keywords: Habitus, Capital, Tourism Development, Tourism Sociology